Trends in age‐specific incidence, mortality, and DALYs of female breast cancer from 1990 to 2021 - Subhadra Priyadarshini; Kunja Bihari Panda (Aging Medicine)
Abstract Objectives Breast cancer is a leading cause of morbidity and mortality among women worldwide. This study aims to analyze the trends in breast cancer incidence, mortality, and disability‐adjusted life years (DALYs) across different age groups from 1990 to 2021, and to project the mortality rate for the next decade. Methods Global breast cancer data were analyzed, focusing on three distinct age groups: 15–49 years, 50–69 years, and 70+ years. Joinpoint regression analysis was used to identify periods of significant changes in cancer rate trends (joinpoints). Age‐specific annual percent changes (APC) and average annual percent changes (AAPC) were calculated to identify trends over time. Additionally, an autoregressive integrated moving average (ARIMA) model was employed to forecast future mortality rates. Results The overall incidence of breast cancer increased significantly with an AAPC of 1.6% from 1990 to 2021. The highest increase was observed in the 15–49 years age group (AAPC: 1.3%), while the 70+ years age group showed the lowest increase (AAPC: 0.2%). Mortality rates exhibited a complex pattern, with a modest overall increase (AAPC: 0.8%), a slight increase in the 15–49 years age group (AAPC: 0.4%), and decreases in both 50 and 69 years (AAPC: −0.4%) and 70+ years age groups (AAPC: –0.3%). DALY rates increased slightly overall (AAPC: 0.7%), primarily driven by the 15–49 years age group (AAPC: 0.4%), while the older age groups showed a declining trend (AAPC: −0.4%). Conclusion Incidence rates are rising across all age groups, with the highest increase observed among younger women (15–49 years). In contrast, older age groups (50 + years) are experiencing improvements in mortality and DALYs. These findings underscore the need for targeted public health interventions, enhanced screening practices, and ongoing advancements in breast cancer treatment to address the evolving burden of this disease across different age groups.